Studies in Health Technology and Informatics Volume 18 - Interactive Technology and the New Paradigm for Healthcare - Morgan, Karen (IOS Press, 2014)
We are in the midst of an Awakening, as Medicine makes the transition from the Industrial Age to the Information Age. We have realized that most information a health care provider needs can be acquired in electronic form (images, scans, vital signs, the medical record). And with the emergence of teleoperation, we can leverage the power of the advanced information tools of software (AI, 3-D visualization and decision support), hardware (high per - formance computing) and networking (the information superhighway). All this will enhance the skills of the health care provider beyond mere physical limitations to enable a quality of care previously considered unachievable. Better access will be provided through remote telemedicine. Lower cost will be achieved through flexible manufacturing, just-intime inventory, and best-in-class business management. Clearly, now is the most exciting time in the history of Medicine, and the researchers and innovators of today are the prophets of the next generation of health care.